Free to become martyrs? The right to refuse medical treatment on religious grounds in a comparative perspective (Stato, Chiese e pluralismo confessionale, 2016)
Article peer reviewedSUMMARY: 1. Aim of the study - 2. Defining medical treatment- 3. Treatment, consent and “religious grounds” - 4. The right to express one’s religion and medical consent - 5. The legitimate limitations on the right to refuse a treatment on religious grounds - 6. Capacity to refuse a treatment - 7. The genuineness of consent - 8. Refusal and children’s best interest – 9. Conclusive remarks. ABSTRACT: This study focuses on the right of patients to refuse medical treatments on religious grounds and on the (supposed) right to the parents to refuse medical treatments on behalf of their children, emphasizing the links and connections between the freedom of religion, the right to self-determination and the right to refuse medical treatment based on religious motivations. After a comparison between the norms devoted to rule the exercise of these rights in the English (and Welsh) and Italian legal systems, the article suggests that the approach of medical staff towards a Refusal of Medical Treatment on Religious Grounds ought to start an intercultural process. This process ought to be a cross-cultural dialogue devoted not only to translate medical language in a language which can be fully understood by the patient, but also to create a reciprocal comprehension between the (mainstream) ethnocultural communication codes and instances of the staff and the (nondominant) ethnocultural (and religious) communication codes and instances of the patient (or of his/her parents).
Keywords: Obiezioni di coscienza